Emerging Trends In Immunotherapy: Evaluating Novel Biologic Agents For Autoimmune Disorders (The Review of Diabetic Studies, 2025)
Immunotherapy had revolutionized the management of autoimmune disorders by targeting specific immune pathways rather than relying solely on broad immunosuppression. This review examined emerging trends and novel biologic agents that had reshaped therapeutic strategies in diseases such as rheumatoid arthritis, multiple sclerosis, psoriasis, and inflammatory bowel disease. Advances in monoclonal antibodies, fusion proteins, cytokine inhibitors, and checkpoint modulators had provided greater efficacy and improved safety profiles compared to traditional therapies. The development of biologics such as TNF-α inhibitors, IL-6 antagonists, and JAK inhibitors had significantly reduced disease progression and improved quality of life. Furthermore, innovative approaches, including bispecific antibodies, CAR-T cell therapy, and nanobody-based treatments, had shown promise in overcoming resistance to conventional immunomodulators. Despite these achievements, limitations persisted, including high treatment costs, immunogenicity, secondary infections, and long-term safety uncertainties. Future research aimed to refine precision immunotherapy through personalized treatment selection, biomarker-guided monitoring, and integration of pharmacogenomic insights. The emergence of AI-based predictive models and nanotechnology-driven delivery systems was expected to enhance therapeutic precision and patient outcomes. Overall, biologic immunotherapy had marked a paradigm shift in autoimmune disease management, paving the way toward targeted, durable, and individualized treatment strategies.